PERSEPSI GURU TERHADAP PEMBINAAN KOMPETENSI PROFESIONAL GURU OLEH KEPALA SEKOLAH DI SMK SE-KECAMATAN LUBUK BEGALUNG PADANG - Dina Melani (Universitas Negeri Padang, 2015)
The purpose of this research is to study how the perception of teacher’sabout development of professional competence of teacher’s by principals at vocational school in the district of Lubuk Begalung Padang. The population is 345 and the sample is 89 by using simple random sampling. The instrument of this research is using statement with likert scale models that have beentested. The data is analyzed trough average score. The resultsof this research is perception of teacher’s about development of professional competence of teacher’s by principals at vocational school in the district of Lubuk Begalung Padang still in enough category.Key word: Development, Professional Competence of Teacher’sPERSEPSI GURU TERHADAP PEMBINAAN KOMPETENSI PROFESIONAL GURU OLEH KEPALA SEKOLAH DI SMK SE-KECAMATAN LUBUK BEGALUNG PADANG Dina Melani Jurusan Administrasi Pendidikan FIP UNP Abstract The purpose of this research is to study how the perception of teacher’sabout development of professional competence of teacher’s by principals at vocational school in the district of Lubuk Begalung Padang. The population is 345 and the sample is 89 by using simple random sampling. The instrument of this research is using statement with likert scale models that have beentested. The data is analyzed trough average score. The resultsof this research is perception of teacher’s about development of professional competence of teacher’s by principals at vocational school in the district of Lubuk Begalung Padang still in enough category. Key word: Development, Professional Competence of Teacher’s